How Parents Involved in Their Children’s Trial? A Book Review ‘Peranan Orang Tua dalam Proses Persidangan Tindak Pidana Perjudian yang Dilakukan oleh Anak’, Lanka Asmar, 2017, CV Mandar Maju, Bandung, 181 Pages, ISBN: 978-979-538-460-1 - Hayati, Zulva (Indonesian Journal of Advocacy and Legal Services, 2020)
The role of parents in a Juvenile Court can influence a judge's decision about a criminal penalty that dropped on to a childrens that done a gambling crime. Focus on the description of a gambling crime, children age, and criminal penalty that given to a children, and the rights of children as a defendant. The book of ‘Peranan Orang Tua Dalam Proses Persidangan Tindak Pidana Perjudian Yang Dilakukan Oleh Anak’ presents how parents deal with children who are dealing with the law and how the role of law enforcers, especially child judges, response to the presence of parents in the proceedings of children. The author will describe the factors that cause children's involvement in gambling cases, the importance of the role of parents in this case, and the judge's decision on the case that has occurred.